Penguatan Karakter Kebangsaan bagi Siswa di SMA Negeri 1 Kabila: Pengabdian - Sukarman Kamuli; Ariyanto Nggilu; Ahmad Karim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to strengthen the national character of SMA Negeri 1 Kabila students in facing the increasingly complex challenges of globalization. The activity was carried out through the method of lectures and interactive dialogues which were carried out offline with three main stages, namely observation, material delivery, and evaluation. Observations were carried out to identify the initial level of students' understanding of national values. The material delivery stage is carried out through a combination of lectures and interactive dialogues to encourage students' active involvement in the learning process, while the evaluation stage aims to assess the improvement of their understanding and appreciation of national values. The results of the activity showed that the participants had a good basic understanding of the importance of national character and showed awareness of the need for continuous coaching. Nevertheless, there are still some challenges, such as a lack of a deep understanding of the nature of nationalism, diverse perceptions of the influence of globalization, and gaps between conceptual understanding and the application of national values in daily life. This activity concluded that although the foundations of student understanding have been formed, a sustainable and comprehensive approach is needed to transform national values into tangible behaviors. The recommendations proposed include the development of a follow-up program that focuses on internalizing values through concrete practices, intensive mentoring, and strengthening the role of schools as an environment of habituation. Overall, this service activity has a positive impact on increasing students' national awareness, strengthening their understanding of the nation's noble values, and equipping them with the ability to respond critically to the flow of globalization without losing their identity as an Indonesian nation.